2009
DOI: 10.1123/jsep.31.6.761
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Attentional Control, and Performance Impairment in Penalty Kicks

Abstract: The current study sought to test the predictions of attentional control theory (ACT) in a sporting environment. Fourteen experienced footballers took penalty kicks under low-and high-threat counterbalanced conditions while wearing a gaze registration system. Fixations to target locations (goalkeeper and goal area) were determined using frame-by-frame analysis. When anxious, footballers made faster first fixations and fixated for significantly longer toward the goalkeeper. This disruption in gaze behavior broug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
148
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(166 citation statements)
references
References 37 publications
11
148
0
6
Order By: Relevance
“…The experimental manipulations produced a sustained effect on anxiety levels, as scores were reported by the participants following every block of trials resulting in the production of a mean score. The different procedure employed may be the reason for the relatively small change in anxiety across blocks when compared with other published reports (e.g., Wilson et al, 2009). …”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The experimental manipulations produced a sustained effect on anxiety levels, as scores were reported by the participants following every block of trials resulting in the production of a mean score. The different procedure employed may be the reason for the relatively small change in anxiety across blocks when compared with other published reports (e.g., Wilson et al, 2009). …”
Section: Discussionmentioning
confidence: 45%
“…Each item required a response on an 11-point Likert scale from 'not worried' (1) to 'worried' (11) for cognitive anxiety; 'not tense' (1) to 'tense' (11) for somatic anxiety; and 'not confident' (1) and 'confident' (11) for self-confidence. The MRF-3 was incorporated to keep in line with previous research into the application of PET and ACT to sport (see Wilson, Wood, & Vine, 2009;Wood & Wilson, 2011).…”
Section: Design and Measuresmentioning
confidence: 99%
“…Such shifts in attention can lead to a decrease in task efficiency, and possibly performance, as less attention is available for actual task execution. As an example, penalty kick performance in soccer players deteriorated when state anxiety was induced (Wilson, Wood, & Vine, 2009b). In line with attentional control theory, this drop in performance was accompanied by shifts in visual attention from the goal target area towards the goalkeeper, which is a potential threat to scoring a penalty in soccer.…”
Section: Introductionmentioning
confidence: 66%
“…A number of studies have found supporting evidence for the predictions of ACT on gaze behavior [4,5,6,7,8]. Anxiety has been shown to increase the frequency of fixations on goal-irrelevant stimuli [8] and to reduce the duration of ordinarily long target-focused fixations [5,9,7].…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety has been shown to increase the frequency of fixations on goal-irrelevant stimuli [8] and to reduce the duration of ordinarily long target-focused fixations [5,9,7]. Recently, two studies have examined the effects of anxiety on gaze behavior in aviation tasks [10,11].…”
Section: Introductionmentioning
confidence: 99%